Continuous Closed-circuit Removal of Methylene Blue and Methyl Orange Dyes by Activated Pomelo Peel BiocharAlginate Hydrogel Beads - Mai Lien Tran (International Journal of Renewable Energy Development, 2026)
The successful fabrication of composite hydrogel beads was realized through the integration of activated pomelo peel biochar (PBC) into a sodium alginate (NaAlg) polymeric matrix, a process facilitated by Ca2+-induced ionic cross-linking. Morphological evaluations of the resulting material confirmed a highly textured surface, demonstrating that the PBC particles were effectively and uniformly embedded within the alginate framework. In terms of performance, the composite formulation consisting of 3.3% (w/v) PBC and NaAlg exhibited exceptional adsorption affinity for both methylene blue (MB) and methyl orange (MO) dyes. The equilibrium data showed a superior fit to the Langmuir isotherm model, which implies a predominantly homogeneous monolayer adsorption process; under continuous flow conditions at 30°C, the maximum adsorption capacities were recorded at 279.68 mg/g for MB and 179.02 mg/g for MO. Furthermore, kinetic modeling indicated that the adsorption behavior strictly followed a pseudo-second-order mechanism, suggesting that the rate-limiting step is governed by chemisorption rather than physical forces alone. The fundamental removal mechanism is believed to be a synergistic interplay of various physicochemical forces, including pore-filling within the biochar structure, p-p interactions between aromatic rings, and the formation of hydrogen bonds between the dye molecules and the composite surface.